# I don't understand this math question, can someone explain it? 0.6(y + 3)=4.8

*print*Print*list*Cite

### 3 Answers

This is an equation which needs to be solved for y. To solve the equation, we need to do the same thing to both sides in order to isolate y, or leave y on the left side and bring everything else to the other sides.

In this equation, on the left side we have 0.6 times (y + 3), so we might start by isolating parenthesis and dividing both sides of the equation by 0.6:

`(0.6(y+3))/0.6 = 4.8/0.6`

Now we have to perform the division of decimals on the right side. To do this, both top and bottom of 4.8/0.6 can be multiplied by 10, which moves the decimal point to the right in both numbers:

`4.8/0.6 = 48/6=8`

So we have y + 3 = 8. Now we can subtract 3 from both sides and get

y = 5.

**The answer is y = 5.**

Hi this is simple

see its like this

given

(0.6)(y + 3)=4.8

both 0.6 and 4.8 are with one decimal so multiply with 10 on both sides

=> 10*(0.6)(y + 3)=4.8*10

=> **(10*(0.6))** (y + 3)=**(4.8*10)**

=> 6(y+3) =48

we know 6 table , so 6 x 8 =48

=> **6**(y+3) =** 6** * 8

cancel 6 on both sides we get

=> y+3=8

=> y=8-3

so **y=5**

This math question is asking to solve for the value of a variable, `y` .

In order to solve for this variable, you can first **divide**.

For **division**, you *divide* a certain value from both sides of the equation. When I say "both sides," I'm saying on both the left and right of the equal sign. You need to do this to **both sides** in order to maintain that an equal sign shows that both sides are equal to each other.

So, in this case,

0.6(y + 3)=4.8 is the given equation.

With dividing, you can divide both sides of the equation by 0.6. So why not do so? When you divide one side by 0.6, it destroys the 0.6 value, so all that is left on the left side of the equal sign is y+3.

y+3=4.8/0.6

Now, shown in the newly transformed equation above, you **must** divide the right side of the equation by 0.6, as well.

With that, you know that 4.8/0.6=8.

Here's how the new equation looks.

y+3=8

It is much simpler now. You just got over the hard part.

You want the **full value** of **y,** not just to know what y and something else equals. What you have in the equation above now is that y PLUS 3 equals 8. You need the number that represents just y by itself, not with that +3.

So, what do you think you can do?

You can subtract 3 from **both sides** of the equation! Remember that with algebra, whatever you do on one side, you MUST do to the other. You do not want some weird nonsensical equation such as 1=2 popping up and ruining the laws of math, do you?

So with that, on the left side, you subtract 3-3=0, so that's gone. On the right side, you do the same thing. 8-3=5.

Our new equation, happens to be our last!

**y=5**.

What happened to the 3-3, you may ask? 3-3=0, so when that's the case, there's no need to write anything in, since 0 doesn't carry any weight!

I hope I helped! Algebra is tough at first, but once you've got it, everything else is easy as pie!

` `

` ` ` `